Extent of Collaboration in Building Academic – Service Partnerships in Nursing - Tuppal, Cyruz P; Renosa, Mark Donald; Al Harthy, Said (Nurse Media Journal of Nursing, 2016)
Background: There is a growing concern in the nursing service industries to expand the roles of nurses. A well-developed and planned collaboration between the academic and services in nursing is required. Purpose: This study investigated the extent of collaboration in building academic-service partnerships based on the perceptions of the students, faculty, staff nurses, and nursing administrators. Methods: This study employed a descriptive research design to obtain a thorough picture about the extent of collaboration in building academic and service partnerships. The majority of the participants (n=500) were staff nurses (n=232, 46.4%) from 5 hospitals, students (n=160, 32%) and faculty (n=62, 12.4%) from 7 schools who were informed, consented and selected using a purposive sampling. A questionnaire was used to describe the extent of collaboration. Descriptive statistics such as mean, standard deviation, frequency, and the percentage were used. Results: Students, faculty, nursing administrators and staff nurses assessed the overall extent of collaboration in building academic-service partnerships to a great extent in terms of nursing education redesign, research collaboration, faculty practice, academic and clinical progression, and workforce development. Conclusion: Despite the fact there was a great extent of collaboration in building academic-service partnerships in nursing, the proposed intervention or enhancement program can be an instrument to strengthen the current status of nursing amidst radical reforms in the healthcare delivery.